Perancangan Software Impedansi Total Sistem Rangkaian Listrik Menggunakan Metode Gabriel Kron - Ratna Atika; Dyah Utari Yusa Wardhani (Universitas PGRI Palembang, 2023)
Calculating the total impedance between two points that are equivalent and connected to a current voltage source still revolves around the discussion using the Wye-Delta transformation, the theory of the Series-Parallel formula, the loop current method and the node or node voltage method. These calculations are still ineffective and take quite a long time for certain complex circuits, because the calculations can only be done manually. So we need a special solution to facilitate us in the calculation process. In this case it is necessary to do a new transformation approach called Transformation [C]. This [C] Transformation Matrix will connect the old and new equivalent circuits. This study uses the Borland C++ Builder program with four kinds of complex circuit conditions tested. From the test results it can be seen that the results of program calculations are the same as the results of manual calculations and are proven to be easier, more effective and efficient than manual calculations which are complicated and require a long and lengthy calculation process. This software is very helpful and can be applied to calculate the total impedance of an electrical circuit system, especially in certain cases of conditioned complicated circuits.